The 2019 European Electoral Campaign
XXXIV, 400 p. 12 illus. in color.
Keywords: The 2019 European Electoral Campaign: in the time of populism and social media examines political advertising during the 2019 elections to the European Parliament, which has become the largest supranational campaign of its kind in the world. Based on a research project funded by the European Parliament, and an archive of more than 11,000 campaign items, the book draws on results from a major content analysis covering every one of the 28 member states involved. The 2019 European Electoral Campaign delivers a unique comparative assessment on the state of political communication within a European Union convulsed by momentous change. This book will be of interest to scholars, researchers and students of political communication, media, political science, history, European (Union) studies as well as a wider readership including politicians, political strategists, and journalists. Edoardo Novelli is Professor at the University Roma Tre, Italy, where he teaches Political Communication and Media Sociology. His research interests focus on political communication, history of propaganda, electoral campaigns and on the relationship between politics, media and images. He is the responsible for the digital archive of Italian political commercials (www.archivispotpolitici.it) and principal investigator of the European Election Monitoring Center 20-23 (www.electionsmonitoringcenter.eu). Bengt Johansson is Professor in Journalism and Mass Communication at the University of Gothenburg, Sweden. His research and teaching focus on political communication and crisis communication. He is currently co-editor of the Journal of Visual Political Communication and is the principal investigator of Swedish Media Election Studies. < Dominic Wring is Professor of Political Communication at Loughborough University, UK. His research and teaching interests are in politics, campaigning, advertising and public relations and recently he co-directed a real-time news media analysis of the 2019 General Election in the UK. .